Comparisons of serum non-transferrin-bound iron levels and fetal cardiac function between fetuses affected with hemoglobin Bart’s disease and normal fetuses - Jatavan, Phudit; Sekararithi, Rattanaporn; Jaiwongkam, Thidarat; Kumfu, Sirinart; Chattipakorn, Nipon; Tongsong, Theera (Frontiers in Medicine, 2023)
Objective To compare the levels of Non-transferrin bound iron (NTBI) in fetuses with anemia, using Hb Bart’s disease as a study model, and those in unaffected fetuses and to determine the association between fetal cardiac function and the levels of NTBI. Patients and methods A prospective study was conducted on pregnancies at risk of fetal Hb Bart’s disease. All fetuses underwent standard ultrasound examination at 18–22 weeks of gestation for fetal biometry, anomaly screening and fetal cardiac function. After that, 2 ml of fetal blood was taken by cordocentesis to measure NTBI by Labile Plasma Iron (LPI), serum iron, hemoglobin and hematocrit. The NTBI levels of both groups were compared and the correlation between NTBI and fetal cardiac function was determined. Results A total of 50 fetuses, including 20 fetuses with Hb Bart’s disease and 30 unaffected fetuses were recruited. There was a significant increase in the level of serum iron in the affected group (median: 22.7 vs. 9.7; p-value: 0.013) and also a significant increase in NTBI when compared with those of the unaffected fetuses (median 0.11 vs. 0.07; p-value: 0.046). In comparisons of fetal cardiac function, myocardial performance (Tei) index of both sides was significantly increased in the affected group (left Tei: p = 0.001, Right Tei: p = 0.008). Also, isovolumetric contraction time (ICT) was also significantly prolonged (left ICT: p = 0.00, right ICT: p = 0.000). Fetal LPI levels were significantly correlated inversely with fetal hemoglobin levels (p = 0.030) but not significantly correlated with the fetal serum iron levels (p = 0.138). Fetal LPI levels were also significantly correlated positively with myocardial performance index (Tei) of both sides (right Tei: R = 0.000, left Tei: R = 0.000) and right ICT (R = 0.013), but not significantly correlated with left ICT (R = 0.554). Conclusion Anemia caused by fetal Hb Bart’s disease in pre-hydropic stage is significantly associated with fetal cardiac dysfunction and increased fetal serum NTBI levels which are significantly correlated with worsening cardiac dysfunction. Nevertheless, based on the limitations of the present study, further studies including long-term data are required to support a role of fetal anemia as well as increased fetal serum NTBI levels in development of subsequent heart failure or cardiac compromise among the survivors, possibly predisposing to cardiovascular disease in adult life.